PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN, KEPERCAYAAN PELANGGAN, LOYALITAS PELANGGAN, DAN KESENANGAN PELANGGAN INDIHOME. STUDI PADA PT TELKOM INDONESIA DATEL PURBALINGGA - Hartanto Setiadi; Niken Widyastuti (Sekolah Tinggi Ilmu Ekonomi SBI, 2022)
This study means to dissect the impact of service quality factors (X1) on customer satisfaction (Y1), customer trust (Y2), customer loyalty (Y3), and customer delight (Y4) Indihome in Purbalingga Regency. The subjects of this research are customers who subscribe to Indihome in Purbalingga Regency taken from 5 sub-districts. This study utilized an example of 93 respondents still up in the air by bunch irregular examining and estimated utilizing the Slovin recipe. Dispersal of the survey utilizing google structure. The scientific device utilized in this study is Structural Equation Modeling (SEM) utilizing the SPSS Amos rendition 22 application program. Therefore, the better the quality of service provided by PT Telkom Indonesia datel Purbalingga to Indihome customers will affect the satisfaction, trust, loyalty and pleasure of indihome customers in Purbalingga Regency